Development and characterization of novel bigels based on monoglyceride-beeswax oleogel and high acyl gellan gum hydrogel for lycopene delivery. (15th December 2021) - Zhu, Qiaomei; Gao, Jianbiao; Han, Lijun; Han, Kexin; Wei, Wei; Wu, Tao; Li, Jinlong; Zhang, Min
Highlights: GMS-Beeswax and gellan gum based bigels exhibited thermoreversible characteristic. Increased oleogel fractions enhanced the firmness and rheological viscoelasticity of bigels. The presence of gellan gum improved the thermal stability of oleogels. Higher contents of oleogel delayed lycopene release from bigel in simulated gastric digestion. Abstract: The aim of present study was to develop novel bigels as a semi-solid vehicle for lycopene delivery. Bigels were prepared by using the mixture of glycerol monostearate (GMS)-beeswax based oleogel and high acyl gellan gum hydrogel in different proportions. The confocal microscopic observations showed that the obtained bigels were oleogel-in-hydrogel, and droplets became larger with increased contents of oleogel. Higher fractions of oleogel increased the mechanical strength (storage modulus, firmness) of bigels. According to the rheological results, all bigels exhibited solid-like characteristics since the storage modulus were larger than loss modulus. DSC results showed that the melting temperature of bigel was higher than that of oleogel. During in vitro simulated gastrointestinal digestion, the total release percentages varied from 60% to 80%, and a higher content of oleogel within bigels could slower down the release of lycopene, suggesting that a higher proportion of oleogel was beneficial for delivery of fat-soluble nutraceuticals.